Klasifikasi Pneumonia pada Chest X-Ray Paru-paru dengan Ekstraksi Fitur Local Binary Pattern Menggunakan Support Vector Machine - Hafiz Irsyad; Dina Mariana (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2021)
Pneumonia is a type of lung disease caused by bacteria, viruses, fungi, or parasites. One way to find out pneumonia is by X-ray or x-ray. X-ray results will be analyzed by experts in the field to find out whether there is pneumonia or not. This study aims to classify the x-ray results whether there is pneumonia or normal. The method used for the classification of Support Vector Machine (SVM) and Local Binary Pattern (LBP) feature extraction. Stages carried out in the image before the classification are Cropping and Resize, then feature extraction using Local Binary Pattern and in classification using Support Vector Machine produces the best accuracy of 65.63%. Keywords : Pneumonia, Chest X-Ray, LBP, SVM